(untitled) (Balneo and PRM Research Journal, 2024)
The research investigates how cardiac rehabilitation impacts life quality in elderly heart failure patients. Older patients often encounter distinctive issues, such as other health conditions and age-linked frailty, affecting their ability to join and gain from rehab programs. This study examines customized rehab plans to meet these needs, which entail using both traditional and new methods like telerehabilitation and activities such as Tai Chi and yoga. Results show that specific rehab programs notably improve functional ability and cut hospital stays for elderly heart failure patients. Also, home-based rehab plans, like the REACH-HF program, appear cost-effective, boosting life quality and reducing health problems. Telerehabilitation has shown to expand access to rehab services, especially aiding elderly patients who struggle to attend on-site programs. This study also asseses the improvement in quality of life, namely the physical and psychological health, such as the augmentation/improvement of patients’ exercise tolerance, participation in social activities or even the increased desire of taking care of themselves. The research highlights the significance of including risk understanding, precise nursing activities, and diverse physical exercises to enhance involvement and commitment, improving results and patient happiness. These findings support the ongoing creation and execution of patient-focused cardiac rehab strategies to better the overall health and well-being of elderly heart failure patients.